Learning Natural Resources And Energy Resources Using Powtoon As Based Video Media - Upadana, I Putu Adi; Rati, Ni Wayan; Gading, I Ketut (Universitas Pendidikan Ganesha, 2021)
The research conducted based on online learning during Covid-19 Pandemic. The use of less innovate learning media has an impact on student's interest and understanding to the material. This type of research is development research. The research objective of this study is to develop learning videos. The research is limited to development, due to Covid-19 Pandemic that could not involve a lot of students. The type of research used is research and development. The research used questionnaire method to collect the data and assessed two lectures and two teachers. The instrument used to measure the level of acceptance of the learning videos is rate scale in the form of an assessment sheet from the experts. After the data has been finish to be collected, then it continued to analyse using 2x4 cross tabulation gregory formula to determine the acceptability of the developed learning videos. The analysis results score from the four experts was 1.00 and it qualifies as a very high product acceptance qualification. Based on this analysis, it can be concluded that the learning videos developed are valid and can be used in the learning process especially for 4th grade elementary school students.